Application of an LC‐MS/MS method to the pharmacokinetics of TM‐2, a potential antitumour agent, in rats. Issue 6 (10th September 2014) - Men, Lei; Zhao, Yunli; Lin, Hongli; Yang, Mingjing; Liu, Hui; Shao, Yanjie; Fan, Ronghua; Tang, Xing; Yu, Zhiguo
<x xml:space="preserve">Abstract</x> TM‐2 is a novel semi‐synthetic taxane derivative, selected for preclinical development based on its greater anticancer activity and lower toxicity compared with docetaxel. In this study, a rapid and sensitive analytical method based on ultra performance liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) has been developed for the determination of TM‐2 in rat plasma. The biological samples were extracted with methyl tert‐butyl ether and separated on a C18 column (50 mm × 2.1 mm, 1.7 µm) using a mobile phase consisting of acetonitrile and 2 mM ammonium acetate. The standard curves were linear over the range 5–1000 ng/mL in rat plasma. The precision (relative standard deviation, RSD, %) were within 14.5%, and the accuracy (relative error, RE, %) ranged from −1.56 to 2.36%. Recovery and matrix effect were satisfactory in rat plasma. The validated method was successfully applied to pharmacokinetic studies after intravenous administration of TM‐2 to rats. The pharmacokinetics of TM‐2 in rats were characterized by a large volume of distribution and a long half‐life of elimination after single dose (4, 8, and 16 mg/kg), and a good correlation was observed between AUC and dose. The preclinical data will be useful for the design of subsequent trials of TM‐2. Copyright © 2014 John Wiley & Sons, Ltd.